ADMINISTERED ENTITLEMENTS: COLLECTIVE BARGAINING TO AFFIRMATIVE ACTION. Issue 1 (2021) - Moreno, Paul
Abstract: This essay tells the story of the development of two of the most significant and controversial entitlement programs in twentieth-century U.S. history—collective bargaining and affirmative action. It focuses on the nexus between them—how New Deal empowerment of labor unions contributed to racial discrimination, and thus fed the Great Society race-based programs of affirmative action. The evolving relationship between the courts and the bureaucracies is emphasized, particularly how the judiciary went from an obstacle to an enabler of the entitlement state.